Redistribusi Pendapatan : Peran BAZNAS pada Ketimpangan dan Kemiskinan di Indonesia - Khasanah, Miftakhul Fauziyah; Eka Ristanti, Frida; Nur Asiyah, Binti; Mashudi, Mashudi (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
This study analyzes the role of zakat in promoting social justice and income redistribution in Indonesia, using BAZNAS National financial reports from 2022–2023 as a case study. Employing a descriptive quantitative approach, the research evaluates collection efficiency, distribution effectiveness, asnaf allocation, and the estimated impact on poverty and inequality. The findings show an 18.9% increase in zakat collection, though still low relative to national potential (CER 0.28%). Distribution effectiveness reached 78.24%, with the largest allocations assigned to the fakir and fisabilillah categories. The average transfer per beneficiary amounted to Rp619,380 (1.18× the national poverty line), indicating the effectiveness of zakat as a micro-level redistributive tool. However, its macro-level impact on reducing inequality remains limited. The results highlight the need for greater collection scale.